Implementation of Curriculum Development and Application at Madrasah Aliyah Nurul Islah, Sukabumi Regency - Sukanti, Lina (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2023)
Research Objectives To find out (1). The Concept of Curriculum Development at Madrasah Aliyah Nurul Islhah, Sukabumi Regency. (2). Implementation of curriculum development at Madrasah Aliyah Nurul Islhah. The objects of this research are the head of Madrasah, deputy head of Madrasah curriculum, teachers, documentation and literature related to curriculum development. The research method used is a descriptive qualitative approach. Data collection techniques include in-depth interviews, field observations and documentation studies. The research results show that (1). Teachers at Madrasah Aliyah Nurul Islhah Sukabumi Regency have not all met academic quality at the madrasah level education unit, some teachers have completed undergraduate education (S1), according to academic qualifications there are 15 people who have not graduated as many as 10 people are in the process of studying. All teachers are involved in developing the curriculum with the main discussion on the concept of curriculum development which includes the principles of curriculum development, principles of curriculum development. Curriculum development is goal-oriented, relevant, effective, efficient, flexible, integrated and sustainable, based on the national, psychological and sociological philosophy. (2). Implementation of curriculum development consists of annual programs, semester programs, learning implementation plans and minimum completeness criteria.